High Intensity Resistance Exercise Training to Improve Body Composition and Strength in Older Men With Osteosarcopenia. Results of the Randomized Controlled Franconian Osteopenia and Sarcopenia Trial (FrOST) - Kemmler, Wolfgang; Weineck, Markus; Kohl, Matthias; von Stengel, Simon; Giessing, Jürgen; Fröhlich, Michael; Schoene, Daniel (Frontiers in Sports and Active Living, 2020)
Considerably decreased muscle mass and function are subsumed under “sarcopenia,” a geriatric syndrome. Dedicated exercise programs maintain muscle mass and function; however, due to the limited enthusiasm of older adults to exercise, it is important to generate low-threshold interventions for this vulnerable cohort. Thus, the primary aim of this study was to determine the effect of low volume/high intensity resistance exercise training (HIT-RT) combined with protein supplementation on body composition and strength in older men with sarcopenia and osteopenia (osteosarcopenia). Forty-three community-dwelling (cdw) older men (78 ± 4 years) with osteosarcopenia were randomly allocated to a consistently supervised HIT-RT (n = 21) or an inactive control group (CG, n = 22). HIT-RT scheduled a single set protocol with high intensity and effort applied twice a week for 36 weeks so far. Both groups were supplemented with Vit-D (800 IE/d), calcium (1,000 mg/d) and whey-protein (CG: 1.2 vs. HIT-RT: 1.5–1.7 g/kg/d). Study endpoints were body composition (dual-energy x-ray absorptiometry) and maximum isokinetic hip/leg-extensor strength (MIES) by leg-press. After 36 weeks, one participant who developed prostate cancer after inclusion in the study (HIT-RT) and two participants who lost interest (CG, HIT-RT) quit the study. Attendance rate for HIT-RT averaged 93 ± 5%. Total and thigh lean body mass (LBM) significantly (p < 0.001) increased in the HIT-RT and was maintained in the CG (p = 0.46 and 0.37). Differences between the groups for changes of total and thigh LBM were pronounced (p < 0.001; SMD d′ = 1.17 and 1.20). Total and abdominal body fat percentage decreased significantly in the HIT-RT (p < 0.001) and increased in the CG (p = 0.039 and p = 0.097). Intergroup differences were significant (p < 0.001; SMD: d′ = 1.35 and 1.28). Finally, MIES was maintained in the CG (p = 0.860), and improved significantly (p < 0.001) in the HIT-RT. Differences between the groups were significant (p < 0.001, SMD: d′ = 2.41). No adverse effects of the intervention were observed. In summary, the HIT-RT/protein protocol significantly affected body composition and strength in cdw men 72 years+ with osteosarcopenia. In the absence of negative side effects, the intervention was feasible, attractive and time effective. Thus, we conclude that supervised HIT-RT might be an exercise option for older men.